Cyberbullying Suatu Problem Kesadaran Kebebasan Manusia dalam Bermedia Sosial Perspektif Filsafat Armada Riyanto - Awur, Raimundus; Armada Ryanto; Mathias Jebaru Adon (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper examines human actions within social media interactions, with a particular emphasis on the phenomenon of cyberbullying from the perspective of ethical philosophy. The focus of this study is not on the entire scope of ethics in human life, but specifically on evaluating whether cyberbullying can be categorized as morally good or bad according to ethical principles. In everyday life, such actions are often carried out unconsciously by the perpetrators, and many even deny having committed them, due to a lack of understanding about the various forms of cyberbullying. This study employs a qualitative method in the form of a literature review, analyzing various scholarly works and previous studies to explore how ethical philosophy can serve as a framework for assessing the moral value of human behavior in digital spaces. Through this approach, the paper aims to provide a deeper ethical understanding of cyberbullying and to foster critical awareness within society in evaluating and reflecting upon online behavior in contemporary social life.